RESEARCH OF THE SYNTHETIC, PHYSICAL AND CHEMICAL PROPERTIES OF 3-ALKYLSULFONYL-5-(CHINOLINE-2-YL, 2-HYDROXYCHINOLINE-4-YL)-4-R -2,4-DIHYDRO3N-1,2,4-TRIAZOLES 1 - Tm, Kaplaushenko; Oi, Panasenko; Yu, Kucheryavy (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Fundamental research in pharmacy and medicine have shown that drugs, which are based on nucleus of the 1,2,4-triazole, have a wide range of biological effects. Derivatives of this heterocyclic system have well-known Ukrainian clinicians and the world scientists due to its antifungal, antidepressant, anticancer, cardio- and hepatoprotective properties. The pharmacological activity of most organic compounds depends on several different factors, including bioavailability of the substance. Hence, it is very important to consider the results of the synthetic and biological researches and established dependence of structure on the biological action when scientists model new molecules or improve pharmacological properties of an existing structure. One of the important social and economic problems of the pharmaceutical industry is the implementation in practice of new drugs that could compete with expensive imported drugs. In recent times, 1,2,4-triazole-3-thioderivatives take attention of compatriots and scientists of foreign countries who are working on finding bioactive compounds including heterocyclic systems. The structure, physical and chemical properties, pharmacological activities of 1,2,4-triazoles, and their 3-thioderivatives are understudied. Hence, the study of that will be actually and novelty for modern science. The main purpose of our research is synthesis of 3-alkylsulfonyl-5-(chinoline-2-yl, 2-hydroxychinoline-4-yl)-4-R1-2,4-dihydro-3N- 1,2,4-triazoles, studying of its physical and chemical properties. Methods: The initial compounds have been synthesized previously using known in literature techniques. Oxidation of the sulfur atom of the synthesized compounds to the hexavalent condition was carried out adding solution of hydrogen peroxide. Results: The structure of the obtained compounds was determined with the modern physical and chemical analysis methods: Element analysis, infrared-spectrophotometry, and their individuality with thin layer chromatography. Conclusions: Prospect of the further researches is determination of acute toxicity and next studying of pharmacological properties of the synthesized compounds. Keywords: 1,2,4-triazoles, Synthesis, Chemical properties, Chinoline.